Multicenter application of a nursing workload measurement scale in adult hospitalization units - María Fuensanta Hellín Gil; Marzena Mikla; Ana Myriam Seva Llor; María Dolores Roldán Valcárcel; Francisco Javier Ibáñez-López; María José López Montesinos (International Journal of Nursing Sciences, 2022)
Objectives: The study aimed to the multicenter application of a nursing workload measurement scale in the internal medicine and surgery adults hospitalization units. Methods: The study design was a multicenter, observational, and descriptive study. A multicenter application of the MIDENF® nursing workload measurement scale was carried out, which consists of 21 items, and covers the four nursing functions (patient care items, teaching, manager, and researcher), in units of hospitalization of adults of internal medicine and surgery of four different hospitals. Each item contains one or more of the nursing interventions of Nursing Interventions Classification (NIC) and has an assigned time, after comparing the real time it takes to perform each intervention with the North American Nursing Diagnosis Association (NANDA) standardized time. The study was carried out during nine months of the year 2020, measuring two days each month in the three work shifts (morning, evening, and night) to all patients admitted on the days of measurement in the indicated units. Results: The descriptive and inferential analysis of 11,756 completed scales, 5,695 in general surgery and 6,061 in internal medicine, showed a greater care load for the two units during the morning shift (227,034 min in general surgery, 261,835 min in internal medicine), especially in the items of “self-care”, “medication”, “common invasive procedures”, “fluid therapy”, and “patient and family support”, while the managerial function was similar during the three work shifts in the two units studied, getting values between 57,348 and 62,901 min. In the analysis by shift and unit, statistical significance was obtained both for the total workload and the four nursing functions(P < 0.001). Conclusions: It is shown that the use of validated scales with the standardized language of nursing functions, adapted to the units, provides objective information to adjust the nursing staff to the real situation of care in any hospital and unit where it is applied, improving quality and patient safety.